An evaluation model for urban carrying capacity: A case study of China's mega-cities. (April 2016) - Wei, Yigang; Huang, Cui; Li, Jing; Xie, Lingling
Abstract: China experienced unprecedented urbanization development in the last two decades. During the rapid urbanization, cities have been attracting large population inflows from rural areas, and concentrating a wide range of social and economic activities. However, an over-concentration of population and human activities has lead to severe and diverse challenges for sustainable urban development, such as environmental degradation, poor infrastructure, and inadequate public services etc. Against this backdrop, concepts within urban carrying capacity (UCC) have received growing attention. It provides local government and urban planners key conceptual underpinnings to improve urban sustainability. However, there remain huge ambiguities in its definitions, implications, particularly measurable indicators, and analytic procedures. These deficiencies significantly hamper the effective implications of UCC concepts in routine urban management. Using the mean variance analysis method, this paper aims to establish an integrated UCC analytic framework to improve decision-making on sustainable urban land use and development. 30 representative indicators drawn from literature are selected to systematically evaluate the UCC conditions. 30 provincial capital cities and municipalities in China are selected as data sample. The results reveal several important findings. First, there exists a positive link between the city scale and UCC. Second, this exists a geographical pattern that costal cities have a high UCC than the central and western regions. Third, infrastructural and environmental factors are of salient weights in evaluating the UCC. Through the broad validations in China's mega-cities, this system has demonstrated capabilities of simplifying, appropriately quantifying, and evaluating the complex process of urban planning and management towards sustainability. Highlights: This paper develops an integrated urban carrying capacity (UCC) evolution model. The paper summarizes limitations of existing studies on the topic of UCC. The article systematically compares the pros and cons of related evaluation methods for traditional index evaluation systems. The article evaluated the UCC conditions of 30 provincial capital cities and municipalities in China. This paper reveals several important patterns of UCC in China's mega-cities.